2010
DOI: 10.1248/yakushi.130.1105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antimicrobial Stewardship by Infection Control Team in a Japanese Teaching Hospital

Abstract: The objective of this study is to investigate an eŠect on the antimicrobial appropriate use of the antimicrobial stewardship. We investigated the consumption of injectable antimicrobials from 2001 to 2007 and the administration period of speciˆc antimicrobials (carbapenems, fourth-generation cephalosporins, anti-methicillin-resistant Staphylococcus aureus (MRSA) agents) in the individual patient. Since September 2004, the infection control team at Osaka University Hospital has been promoting appropriate use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
14
0
5
Order By: Relevance
“…conversion (1). Of the 36 included studies, 2 were full CEAs [13,14]; 27 studies reported changes to costs and health outcomes separately [3,5,[8][9][10][12][13][14][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 9 reported only changes to costs [4,6,[15][16][17][18][19][20][21]. Table 1 presents the methods and results for studies that measured only cost outcomes and Table 2 presents the methods and findings of those studies that measured both a clinical as well as a cost outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…conversion (1). Of the 36 included studies, 2 were full CEAs [13,14]; 27 studies reported changes to costs and health outcomes separately [3,5,[8][9][10][12][13][14][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 9 reported only changes to costs [4,6,[15][16][17][18][19][20][21]. Table 1 presents the methods and results for studies that measured only cost outcomes and Table 2 presents the methods and findings of those studies that measured both a clinical as well as a cost outcome.…”
Section: Resultsmentioning
confidence: 99%
“…One study also noted cost savings associated with the reduction in LOS [10]. Ten of the twelve studies reported the TAE [3,8,10,22,23,25,26,[28][29][30], whilst one study reported TAE per admission [24] and one reported findings as TAE per 1000 PDs [27]. One study also specifically mentioned that a saving of $194 160 [3] was achieved by i.v.-to-p.o.…”
Section: Cost Consequence Studies That Measured Clinical Outcomesmentioning
confidence: 99%
“…The antimicrobial therapy based on pharmacokinetics-pharmacodynamics theory is performed progressively, and the administration period of carbapenems became shorter by this action. 12) Although there was no significant change in the annual number of isolated P. aeruginosa, the annual number of MDR P. aeruginosa was markedly decreased by the measures against nosocomial infection. In this study, the total consumption of meropenem was correlated with the rate of meropenem-resistant P. aeruginosa.…”
Section: Discussionmentioning
confidence: 96%
“…Same study and several other studies conveyed that irrational prescription of medicine including antimicrobials possibly will result in poor health status and enormous financial impact for any community or country [57][58][59][60][61]. Antimicrobials alone took the share 30-50% of all prescribed medicine in quite a lot of countries [58,62]. Research Center, Shiraz, Iran reported in Editorial in the most prestigious medical journal the Lancet that "antibiotics are an important front-line instrument in the fight against various infectious diseases.…”
Section: The Islamic Republic Of Iranmentioning
confidence: 98%